PEMBENTUKAN KARAKTER KEBANGSAAN MELALUI PROGRAM LITERASI MELALUI SELF MOTIVATION SEBAGAI UPAYA MENGEMBANGKAN LIFE SKILL DENGAN BERBAGI ILMU DI TK AL-UKHUWAH. - Yessi Mareta Andari Putri; Intan Rachmina Koho; Asri Setiani; Yoyok Cahyono; Manorang Sihotang; Enjang Zaenudin (Publika Citra Media, 2026)
This community service program aims to improve literacy skills, self-motivation, and the formation of national character as an effort to develop life skills in early childhood. The program was conducted at Al-Ukhuwah Kindergarten in Tangerang Regency, where students come from families with low- to middle-income families and limited access to a variety of learning media. The implementation method used a participatory and educational approach through basic literacy activities, storytelling, educational games, and self-motivation tailored to the characteristics of early childhood. The results of the program showed an increase in students' interest in literacy, self-confidence, and social interaction skills. Furthermore, national character values such as cooperation, discipline, and self-confidence began to develop through the activities. This program also had a positive impact on teachers in developing more creative and innovative learning methods. Thus, the Literacy through Self-Motivation program is effective as an effort to shape national character and develop life skills from an early age. Sustainable programs and support from various parties are essential to optimize the results.